1999
DOI: 10.1007/s004280050391
|View full text |Cite
|
Sign up to set email alerts
|

Invariant chain expression in colon neoplasms

Abstract: Invariant chain (Ii) is a chaperone molecule that inhibits binding of endogenous antigens to class II molecules. High levels of Ii in cancer cells may prevent tumour antigen expression with class II and render the tumour less immunogenic. To correlate the expression of Ii and class II molecules in colon carcinomas with the density of tumour infiltrating lymphocytes (TILs), surgical specimens from a total of 48 patients with well-(WDAC), moderately (MDAC) and poorly differentiated adenocarcinomas (PDAC), adenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 18 publications
4
33
0
Order By: Relevance
“…It was then shown that the aggressive in vivo behavior of this cell line could be restored by increasing CD74 levels by transfection (30). An association between pathological dedifferentiation, aggressive clinical behavior, and CD74 expression also has been observed in colon cancer specimens (31). The CD74ϩ/DRϪ phenotype observed in the multiple myeloma cases we studied may have similar implications for the biology of multiple myeloma.…”
Section: Discussionsupporting
confidence: 72%
“…It was then shown that the aggressive in vivo behavior of this cell line could be restored by increasing CD74 levels by transfection (30). An association between pathological dedifferentiation, aggressive clinical behavior, and CD74 expression also has been observed in colon cancer specimens (31). The CD74ϩ/DRϪ phenotype observed in the multiple myeloma cases we studied may have similar implications for the biology of multiple myeloma.…”
Section: Discussionsupporting
confidence: 72%
“…It should be noted that, within the colon, altered expression of MHC and Ii/CD74 has been noted in the vicinity of tumors (Degener et al 1988). A significant number of tumors also exhibit non-coordinate expression with greater amounts of Ii/CD74 than MHC II (Degener et al 1988;Moller et al 1991;Jiang et al 1999). Jiang et al (1999) have demonstrated an association of increased Ii/CD74 expression and poor-grade and intratumoral lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…A significant number of tumors also exhibit non-coordinate expression with greater amounts of Ii/CD74 than MHC II (Degener et al 1988;Moller et al 1991;Jiang et al 1999). Jiang et al (1999) have demonstrated an association of increased Ii/CD74 expression and poor-grade and intratumoral lymphocytes. On the basis of this finding they suggest that excess Ii/CD74 expression might render the tumor less immunogenic by inhibiting antigen presentation.…”
Section: Discussionmentioning
confidence: 99%
“…40 CD74, a transmembrane glycoprotein, acts as a chaperone molecule suppressing immune response by inhibiting the cytoplasmic form of HLA class II molecules from binding to endogenously derived antigen peptides. 25 The overexpression of CD74 has been observed in gastric cancer, 41 colonic adenocarcinoma, 42 melanoma, 43 renal epithelial neoplasms 44 and thymic epithelial neoplasms. 45 These findings have led to the proposal that tumors use CD74 as a mechanism to escape the host immune response.…”
Section: Discussionmentioning
confidence: 99%